Popular and Populist Shakespearean Transcreations in Central and Eastern Europe - Cinpoeş, Nicoleta; Deres, Kornélia; Fabiszak, Jacek; Földváry, Kinga; Schandl, Veronika (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The article discusses the variety of ways in which the terms “popular” or “populist” could be associated with postwar Shakespearean transcreations in the Central and Eastern European region, pointing out how performers and adaptors challenged the canonical, highbrow status of Shakespeare and used his oeuvre as raw material in experimental forms and genres. Following a discussion on the variety of socio-historical contexts which inspired noteworthy popular and/or populist reworkings in several Central and Eastern European countries, the article takes a more in-depth look at a few specific comic genres, particularly the burlesque and the cabaret in a theoretical framework, and concludes by examining post-1989 experimental theatre practices. The publication of the article was supported by the International Visegrad Fund, project no. 22210007, titled “Crossing Borders with Shakespeare since 1945: Central and Eastern European Roots and Routes.” The project is co-financed by the Governments of the Czechia, Hungary, Poland and Slovakia through Visegrad Grants. The mission of the Fund is to advance ideas for sustainable regional cooperation in Central Europe.